A Systematic Review of Neuroprotective Effects of Mangosteen and its Xanthones Against Oxidative Stress and Inflammation - Thew, Hin Yee; Tan, Yong Chiang; Ong, Yong Sze; Goh, Bey Hing; Khaw, Kooi Yeong (Planta Medica, 2025)
Mangosteen has garnered increasing attention for its medicinal properties against oxidative stress and inflammation–two major causative and progressive agents of neurodegenerative diseases. This systematic review explores the antioxidative and anti-inflammatory effects of mangosteen crude extracts and their purified bioactive compounds, highlighting their neuroprotective potential against neurodegenerative conditions.The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) strategy was used to identify studies published in English up to July 2024 across five databases (Cochrane, PubMed, Scopus, Web of Science, and Google Scholar). The Population, Intervention, Comparison, and Outcome (PICO) framework guided the search strategy, and duplicate records were removed using Covidence software. Of the 149 studies screened, 40 met the predefined inclusion criteria and were included in the review. The quality of the included studies was assessed using criteria adapted from the Cochrane Handbook, focusing on risk of bias and methodological rigor.Mangosteen extract and xanthones consistently reduced oxidative markers in various models. Anti-inflammatory effects were evident as mangosteen extract reduced pro-inflammatory cytokines and modulated the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and cyclooxygenase-2 (COX-2) pathways in neuroinflammation models. Xanthones further suppressed inflammatory mediators and enhanced cellular resilience.The in vitro and in vivo results suggested the neuroprotective capabilities of mangosteen extracts and its purified bioactives. Despite that, gaps remain in understanding the potential synergistic effects of these bioactives, their druggability properties, and clinical applicability. Further research, especially clinical trials, will be necessary to further impel mangosteen and its derivatives into therapeutic applications.
Keywords: Garcinia mangostana; Clusiaceae; xanthone; oxidative stress; inflammation